Individualized Risk of Surgical Complications: An Application of the Breast Reconstruction Risk Assessment Score. Issue 5 (May 2015) - Kim, John Y. S.; Mlodinow, Alexei S.; Khavanin, Nima; Hume, Keith M.; Simmons, Christopher J.; Weiss, Michael J.; Murphy, Robert X.; Gutowski, Karol A.
Abstract : Background: Risk discussion is a central tenet of the dialogue between surgeon and patient. Risk calculators have recently offered a new way to integrate evidence-based practice into the discussion of individualized patient risk and expectation management. Focusing on the comprehensive Tracking Operations and Outcomes for Plastic Surgeons (TOPS) database, we endeavored to add plastic surgical outcomes to the previously developed Breast Reconstruction Risk Assessment (BRA) score. Methods: The TOPS database from 2008 to 2011 was queried for patients undergoing breast reconstruction. Regression models were constructed for the following complications: seroma, dehiscence, surgical site infection (SSI), explantation, flap failure, reoperation, and overall complications. Results: Of 11, 992 cases, 4439 met inclusion criteria. Overall complication rate was 15.9%, with rates of 3.4% for seroma, 4.0% for SSI, 6.1% for dehiscence, 3.7% for explantation, 7.0% for flap loss, and 6.4% for reoperation. Individualized risk models were developed with acceptable goodness of fit, accuracy, and internal validity. Distribution of overall complication risk was broad and asymmetric, meaning that the average risk was often a poor estimate of the risk for any given patient. These models were added to the previously developed open-access version of the risk calculator, available athttp://www.BRAscore.org . Conclusions: Population-based measures of risk may not accurately reflect risk for many individual patients. In this era of increasing emphasis on evidence-based medicine, we have developed a breast reconstruction risk assessment calculator from the robust TOPS database. The BRA Score tool can aid in individualizing—and quantifying—risk to better inform surgical decision making and better manage patient expectations.